Somatostatin and SMS 201-995 (octreotide): clinical and therapeutic aspects. - da Silva, P M; Augusto, F (Acta Médica Portuguesa, 1993)
Nowadays, the digestive system, must be considered as an actual endocrinous gland. The authors, after pointing out the pharmacological and immunomodulating actions of endogenous somatostatine, briefly describe a new synthetic octapeptid, somatostatine-analogue, with similar pharmacological effects (octreotide). Finally they stress the therapeutic trials in which the adverse effects, dosage and administration have been studied.